2021
DOI: 10.1038/s41598-021-97054-4
|View full text |Cite
|
Sign up to set email alerts
|

Skull shape abnormalities in ischemic cerebrovascular and mental diseases in adults

Abstract: Morphological changes in the child skull due to mechanical and metabolic stimulation and synostosis of the suture are well known. On the other hand, few studies have focused on clinical conditions relevant for adult skull deformity. We retrospectively reviewed computed tomography (CT) findings obtained from 365 cases that were treated for head injuries, moyamoya disease, cervical internal carotid artery stenosis, and mental diseases, and investigated the morphological changes in the skull associated with these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…12.100 (TeraRecon, San Mateo, CA, USA). The measurement and parameter calculation methods were based on previous studies 7 , 9 . After defining a horizontal plane from a line through the middle of the eye and ear canal, orbital slices parallel to this plane were created by multiplanar reconstruction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…12.100 (TeraRecon, San Mateo, CA, USA). The measurement and parameter calculation methods were based on previous studies 7 , 9 . After defining a horizontal plane from a line through the middle of the eye and ear canal, orbital slices parallel to this plane were created by multiplanar reconstruction.…”
Section: Methodsmentioning
confidence: 99%
“…In a cadaver study, 19 of 65 specimens (29%) showed irregular undulating and thickening of the frontal bone internal surface, of which 5 specimens (26%) were of patients diagnosed with neurological disorders, including Alzheimer's disease, dementia, depression, and PD 6 . Nagaishi et al used computed tomography (CT) to investigate skull morphological changes 7 and showed that cranial shape significantly differed between patients with moyamoya disease, cervical internal carotid artery stenosis, depression, or schizophrenia and control participants. Thus, abnormal skull shape may be related to brain dysfunction and disease.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of congenital malformations of the skull may be encountered. Many clinical presentationsincluding hearing loss, impaired vision, cognitive disability, and mental diseasemanifest in children or adults in association with such malformations [39][40][41]. Early detection of pathological changes and further differential diagnosis and therapy decisions are ascertained with evaluation of the skull.…”
Section: Generalizabilitymentioning
confidence: 99%
“…An earlier study showed the association between tomographic characteristics of the temporal bone and transtemporal window quality on transcranial Doppler ultrasound in patients with stroke or transient ischemic attack [9]. Skull shape abnormalities in ischemic cerebrovascular and mental diseases in adults have also been reported [10]. Optimization of the probe location on the head for neuroimaging/brain simulation thus has added value in various neurostimulation and imaging studies, such as simulation ultrasonic wave propagation and acoustic transmission [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%